The mind and its stories : narrative universals and human emotion - Hogan, Patrick Colm (Studies in emotion and social interaction., 2003)
Hogan argues that the stories people admire in different cultures follow a limited number of patterns determined by cross-culturally constant ideas about emotion. He concludes with a discussion of the relations among narrative, emotion concepts, and the biological and social components of emotion.